Physical Activity as an Adjunct to Compression Therapy on Healing Outcomes and Recurrence in Patients With Venous Leg Ulcers: A Scoping Review Protocol - Qiu, Yunjing; Osadnik, Christian Robert; Team, Victoria; Weller, Carolina Dragica (Frontiers in Medicine, 2021)
Background: Chronic venous leg ulceration is a common and costly clinical issue across the world, affecting up to 3 in 1000 people. Compression therapy is recommended as the gold standard treatment in clinical practice, although a large number of venous leg ulcers remain unhealed after several years. Physical activity may improve healing although there is limited evidence on the effects of physical activity as an adjuvant treatment to compression to improve venous leg ulcers healing and prevent recurrence. Objectives: This scoping review protocol aims to systematically search, appraise, and synthesize quantitative research evidence to assess the effect of physical activity interventions applied in conjunction with compression therapy on venous leg ulcer healing and recurrence. Methods and analysis: We will use the methodology framework suggested by Arksey and O’Malley, Levac et al., the JBI as a guide. We will also follow the three-step search strategy recommended by the JBI to systematic search for relevant published research, ongoing clinical trials and grey literature. Two review authors will independently screen titles and abstracts followed by full-text review to determine final eligibility for inclusion. The search process will be reported using a Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow chart. Characteristics of physical activity interventions, primary outcomes related to ulcer healing and recurrence, and secondary outcomes of interest included quality of life, pain level, adverse effects and economic costs will be extracted and summarized. The review will provide a descriptive account of the findings from included studies. Where appropriate, data will be pooled for a meta-analysis using a random effects model. Discussion: Physical activity interventions represent a low-cost, potentially useful adjuvant treatment to compression therapy for the management of venous leg ulcers. Several gaps in knowledge remain that are answerable via a targeted scoping review. This protocol outlines the rationale, objectives and the planned methodology for conducting the study. Ethics and Dissemination: The scoping review will use data from publicly available sources and ethical approval is not required. Findings from this review will be submitted to a peer-reviewed journal, presented at relevant conferences and disseminated via social media.